Methodological choices affect cancer incidence rates: a cohort study. Issue 1 (December 2017) - Brooke, Hannah; Talbäck, Mats; Feychting, Maria; Ljung, Rickard
Abstract Background Incidence rates are fundamental to epidemiology, but their magnitude and interpretation depend on methodological choices. We aimed to examine the extent to which the definition of the study population affects cancer incidence rates. Methods All primary cancer diagnoses in Sweden between 1958 and 2010 were identified from the national Cancer Register. Age-standardized and age-specific incidence rates of 29 cancer subtypes between 2000 and 2010 were calculated using four definitions of the study population: persons resident in Sweden 1) based on general population statistics; 2) with no previous subtype-specific cancer diagnosis; 3) with no previous cancer diagnosis except non-melanoma skin cancer; and 4) with no previous cancer diagnosis of any type. We calculated absolute and relative differences between methods. Results Age-standardized incidence rates calculated using general population statistics ranged from 6% lower (prostate cancer, incidence rate difference: -13.5/100, 000 person-years) to 8% higher (breast cancer in women, incidence rate difference: 10.5/100, 000 person-years) than incidence rates based on individuals with no previous subtype-specific cancer diagnosis. Age-standardized incidence rates in persons with no previous cancer of any type were up to 10% lower (bladder cancer in women) than rates in those with no previous subtype-specific cancer diagnosis; however, absolute differences were <5/100, 000 person-years for all cancer subtypes. Conclusions For some cancer subtypes incidence rates vary depending on the definition of the study population. For these subtypes, standardized incidence ratios calculated using general population statistics could be misleading. Moreover, etiological arguments should be used to inform methodological choices during study design.